HUBUNGAN MODEL PEMBELAJARAN FLIPPED CLASSROOM DENGAN KEAKTIFAN BELAJAR SISWA MATERI SISTEM PENCERNAAN DI KELAS V SD - Anas Tasya; Destrinelli; Alirmansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the relationship between the Flipped Classroom learning model and student learning engagement in the digestive system topic among fifth- grade students at UPT SDN 11 Padang Ganting. Using a quantitative approach, this correlational study analyzes the relationship between two variables. The sampling technique employed was total sampling, involving all 21 fifth-grade studentsl. Validity and reliability tests confirmed that all items were valid and reliable. The Pearson product-moment correlation test showed a p-value (Sig. 2-tailed) of 0.020, which is less than 0.05. This indicates sufficient statistical evidence to support the existence of a relationship between the flipped classroom model and student engagement. The correlation coefficient was 0.502, indicating a moderately strong positive relationship. This suggests that the more effectively the Flipped Classroom model is implemented, the higher the level of student engagement. In conclusion, the study found a moderately strong relationship between the Flipped Classroom learning model and student engagement in learning about the digestive system among fifth-grade students at UPT SDN 11 Padang Ganting.